Cholinergic modulation of neural networks supports sequential and complementary roles for NREM and REM states in memory consolidation. - Michael Satchell; Edith Butel-Fry; Zahraa Noureddine; Alexis Simmons; Nicolette Ognjanovski; Sara J Aton; Michal R Zochowski (PLoS Computational Biology)
Across vertebrate species, sleep consists of repeating cycles of NREM followed by REM. However, their respective functions, and their stereotypic cycling pattern are not well understood. Using a simplified biophysical network model, we investigate the potential role of cholinergic modulation, acting via the muscarinic receptors, on network dynamics and memory consolidation. We show that low and high cholinergic levels associated with NREM and REM sleep, respectively, may play critical, sequential roles in memory consolidation. The network dynamics that facilitate these roles arise through alteration of neural excitability and changes to network-wide excitatory/inhibitory balance. At low acetylcholine (ACh) levels, reduced activation of inhibitory neurons leads to network-wide disinhibition and bursts of synchronized activity led by engram neurons, driving recruitment of additional excitatory neurons into the engram. In contrast, at high ACh levels, increased network inhibition suppresses firing in all but the most strongly recruited excitatory neurons, pruning the expanded engram population. Together, these results provide a testable hypothesis regarding the role of sleep state-specific cholinergic modulation in the process of memory consolidation.